Perception of the stereokinetic illusion by the common marmoset (Callithrix jacchus) - Clara, Elena; Regolin, Lucia; Vallortigara, Giorgio; Rogers, Lesley (Animal cognition, 2007)
Stereokinetic illusions have never been investigated in non-human primates, nor in other mammalian species. These illusions consist in the perception of a 3D solid object when certain 2D stimuli are rotated slowly in the plane perpendicular to the line of sight. The ability to perceive the stereokinetic illusion was investigated in the common marmoset (Callithrix jacchus). Four adult marmosets were trained to discriminate between a solid cylinder and a solid cone for food reward. Once learning criterion was reached, the marmosets were tested in sets of eight probe trials in which the two solid objects used at training were replaced by two rotating 2D stimuli. Only one of these stimuli produced, at least to the human observer, the stereokinetic illusion corresponding to the solid object previously reinforced. At test, the general behaviour and the total time spent by the marmosets observing each stimulus were recorded. The subjects stayed longer near the stimulus producing the stereokinetic illusion corresponding to the solid object reinforced at training than they did near the illusion corresponding to the previously non-rewarded stimulus. Hence, the common marmosets behaved as if they could perceive stereokinetic illusions.